Inclusive Democracy in Nigeria: The Roles of the Indigenous Languages - Ugwu, Eucharia Okwudilichukwu (European Scientific Journal, ESJ, 2020)
Language is like a chord that binds people together. However, when language issues are not properly handled, they can cause exclusion and division, especially in highly multilingual societies like Nigeria. Thus, language rights are now recognised globally as aspects of human rights. As a dominant and official language in Nigeria, English hastended to exclude many citizens from full participation in developmental activities and life opportunities due to limited access to it. This is irrespective of the fact that one major justification for its promotion, as against the indigenous languages, hinges on the rhetoric of national unity. Unity can hardly be achieved in an atmosphere of marginalisation and widening inequality gap. Given the multilingual and multi-ethnic status of Nigeria, respecting the language rights of the different ethnolinguistic communities is indispensable for mutual and peaceful co-existence and enhanced quality of life. This paper highlights the important roles the indigenous languages could play in making Nigeria a truly plurilingual nation bound by respect for human lives and values, equity and tolerance.